Investigations of the efficiency of a parallel program for construction of the shortest covering of a Boolean matrix - Adamus, Adam; Novikov, Sergey (Studia Informatica. System and information technology, 2019)
The paper presents results of investigations of the efficiency of a parallel program for the solution of the NP-complete problem of constructing of the shortest covering of a Boolean matrix. It was explored dependencies of the time of constructing of the shortest covering from the number processing processors of a cluster and from the dimension of a Boolean matrix.